2013
DOI: 10.1590/s0080-62342013000100003
|View full text |Cite
|
Sign up to set email alerts
|

Pesquisa do estreptococo do Grupo B em gestantes da Zona Leste de São Paulo

Abstract: RESUMO ABSTRACTA retrospec ve, cross-sec onal study of 30 women seen at a Basic Health Care Unit (BHCU) in the Eastern Sec on of São Paulo, using interviews and medical record reviews, to determine how group B streptococcus (GBS) was detected in pregnant women. The pa ents in the studied sample received prenatal care at the UBS and delivered their babies between January 2009 and December 2010. Twenty-three of the women (76.7% of the total) underwent a GBS culture, 82.6% of which yielded a nega ve result and 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
0
6
1
2
Order By: Relevance
“…Samples for culture obtained up to four weeks before delivery have greater sensitivity and specificity to identify maternal colonization by GBS 10 . Studies have shown a high rate of transmission to newborns during childbirth, as well as increased infection and neonatal mortality rate.…”
Section: Introductionmentioning
confidence: 99%
“…Samples for culture obtained up to four weeks before delivery have greater sensitivity and specificity to identify maternal colonization by GBS 10 . Studies have shown a high rate of transmission to newborns during childbirth, as well as increased infection and neonatal mortality rate.…”
Section: Introductionmentioning
confidence: 99%
“…In Brazil, there are some data on maternal GBS colonization showing different rates 6 - 8 , but there is no official recommendation by the Brazilian Health Ministry regarding the GBS screening in all the pregnant women in order to perform prophylaxis. To achieve the adequate prophylaxis, the knowledge of GBS susceptibility to the primarily used drugs in a given population is needed.…”
Section: Introductionmentioning
confidence: 99%
“…The percentage of pregnant women (28.4%), which were GBS carriers at 35–37 weeks of gestation in the present study, corroborates with study conducted by Feuerschuette et al [ 1 ]. Two other studies reported a lower prevalence: 17.4% [ 15 ] and 15.0% [ 16 ]. This variation in GBS maternal detection may be attributable to differences in the applied methodologies to detect GBS and characteristics of the studied populations.…”
Section: Discussionmentioning
confidence: 99%